Proceedings of the 4th International Symposium on Health Research (ISHR 2019) 2020
DOI: 10.2991/ahsr.k.200215.016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Anastatica hierochuntica L. Extract on the Histology of Myometrial Cells and Prostaglandin levels (PGE2, PGF2α) in Pregnant Mice

Abstract: Anastatica hierochuntica L. is well known as a traditional medicine which brings benefit to the final trimester of pregnancy by increase uterine contractions. This study aimed to analyze the effect of A. hierochuntica L. extract on the histology of myometrial cells and prostaglandin levels (PGE2 and PGF2α) of pregnant mice. The mice were divided into three groups: (1) control group, treated by 0.5% CMC solution 10 ml/kg bw/day; (2) two treatment groups that treated by A. hierochuntica L. extract with 100 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Some researchers have hypothesized that the most crucial function of oxytocin is to increase the production of prostaglandins (potent inducers of uterine contractions) by inducing the expression of COX-2 via the activation of the pathway MAPK [3] [45]. Astutik et al demonstrated that administration of the hydroethanolic extract of Anastatica hierochutica to pregnant mice leads to increased prostaglandin levels of PGE2 and PGF2α [46]. Tannins, flavonoids, and saponins were highlighted in uterotonic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have hypothesized that the most crucial function of oxytocin is to increase the production of prostaglandins (potent inducers of uterine contractions) by inducing the expression of COX-2 via the activation of the pathway MAPK [3] [45]. Astutik et al demonstrated that administration of the hydroethanolic extract of Anastatica hierochutica to pregnant mice leads to increased prostaglandin levels of PGE2 and PGF2α [46]. Tannins, flavonoids, and saponins were highlighted in uterotonic plants.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have hypothesized that the most crucial function of oxytocin is to increase the production of prostaglandins (potent inducers of uterine contractions) by inducing the expression of COX-2 via the activation of the pathway MAPK [3,45]. Astutik et al demonstrated that administration of the hydroethanolic extract of Anastatica hierochutica to pregnant mice leads to increased prostaglandin levels of PGE2 and PGF2α [46]. Tannins, flavonoids, and saponins were highlighted in uterotonic plants.…”
Section: Discussionmentioning
confidence: 99%
“…The author obtained articles from the PubMed, Scient Direct, MDPI, Google Schoolar, Research Gate, and Semantic scholar databases to find out which potential studies were appropriate and met the requirements as inclusion criteria. 25,26,27,28,and Indonesia 3,4,9,14,19,20. See Figure 1 for details on study settings. Scientific research on Fatimah Grass or Labisia Pumila was conducted to identify bioactive phytochemicals that contribute to its pharmacological properties.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has proven the effects of fatimah grass water immersion, including increasing the hormone oxytocin, antioxidant, anti-inflammatory, reducing the risk of dyslipidemia, phytoestrogenics, skin collagen synthesis, playing a role in the process of estrogen hormone therapy in menopause, improving lipid profiles, therapy for dysentery, dysmenorrhea 2,3,4,5 . Therefore, the use of Fatimah grass soaking water is still used today because it is considered to have great benefits, especially for women who are more interested in herbal or natural medicines.…”
Section: Introductionmentioning
confidence: 99%